Role of Media in Addressing Local Crises in Building Audience Agenda by Iraqi Satellite Channels - Dr. Muthanna Mohammed Faihan Al-Ghanemi ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
Satellite channels provide news and information to the audience with multiple templates and frames after treating them in light of visions and philosophy intended to deliver their content to the audience, especially when they come to internal or external local crises and disturbances and urgent events, herein, the role appears of the satellite channels in dealing with the news and their keenness to prioritize preference on the topics. Accordingly, the problem of this study has illuminated from the feeling that there is an aspects for questioning to be considered in order to derive accurate scientific results on the main equation of the study (What is the Role of Iraqi Satellite Channels in Addressing Local Crises in Building Audience Agenda?) and then the importance and objectives of the study were determined and the researcher initiated his methodological procedures by identifying the fields of study, its community, type and size of the sample and tools of the study as well as conducting honesty and consistency test.